2014
DOI: 10.1108/bfj-12-2012-0293
|View full text |Cite
|
Sign up to set email alerts
|

SWOT analysis of the truffles market in Greece

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
(98 reference statements)
0
8
0
1
Order By: Relevance
“…The SWOT analysis has also been applied in the horticulture sector, such as tubers. Besides showing weakness and strength, the SWOT analysis can map out the problems related to the opportunities in the sector (Tsitsipati, 2014) and is regarded as one of the most useful tools, as used in Raviv's (2013) research. From the context of the planting media, the paper investigates the strengths, weaknesses, opportunities, and threats involved with the use of various composts in GM.…”
Section: Swot Analysismentioning
confidence: 99%
“…The SWOT analysis has also been applied in the horticulture sector, such as tubers. Besides showing weakness and strength, the SWOT analysis can map out the problems related to the opportunities in the sector (Tsitsipati, 2014) and is regarded as one of the most useful tools, as used in Raviv's (2013) research. From the context of the planting media, the paper investigates the strengths, weaknesses, opportunities, and threats involved with the use of various composts in GM.…”
Section: Swot Analysismentioning
confidence: 99%
“…When the literature is examined in the context of evaluating the gastronomic potential, it is seen that the researches mainly examine the gastronomy tourism or types of gastronomy tourism (such as wine tourism) for the destinations (Iakovou et al, 2009;Tsitsipati et al, 2014;Zaman and Kayserili, 2014;Deniz and Atışman, 2017;Harcsa, 2017;Derčan et al, 2017;Bozkurt, 2018;Cankül and Ezenel, 2018;Bozkurt et al, 2019;Chaigasem and Tunming, 2019;Çabuk et al, 2020;Sormaz et al, 2020;Stockovič et al, 2020). Iakovou et al (2009) aimed to comprehensively analyze the current situation of gastronomy tourism in the Central Macedonia Region (RCM) of Greece.…”
Section: Literaturementioning
confidence: 99%
“…Notwithstanding the role of TLFs in modern economies, as previously noted, little evidence exists about the attitudes and behaviours of young people towards them. Considering the truffle, in particular, only one study of Tsitsipati and Athanasios (2014) has been found which revealed that a typical truffles consumer’s age average is 38 years old and that the main consumers can be found among highly educated people. This suggests the importance of investigating the Millennial segment, in particular students, to add further knowledge to the extant literature.…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%
“…First, TLFs are described in the literature according to a variety of criteria, including geographic or perceived areas of production, cultural criteria, natural history and municipal boundaries or distances (Wenzig and Gruchmann, 2018) and truffle highly reflects these criteria being always included among such products (Balabanova, 2014; Galluzzo, 2015; Pencarelli et al , 2018). Moreover, on a global level, there is an increasing demand for truffle, since its importance is recognised for the valorisation of the rural economy and the economic interest in its promotion is always stronger (Tsitsipati and Athanasios, 2014).…”
Section: Introductionmentioning
confidence: 99%